PENGARUH PENGGUNAAN MEDIA ANIMASI POSTER UNTUK MENINGKATKAN KEMAMPUAN MENGENAL ANGGOTA TUBUH PADA SISWA AUTIS KELAS II SLB - Fatchur Rozi; Nurul Hidayati; Ana Rafikayati (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
This research was motivated by the low ability of second-grade autistic students at SLB Negeri 2 Pasuruan City to recognize and correctly name body parts. The main focus of the research was to evaluate the effect of using Canva-based animated posters on improving these competencies. Using a quantitative approach with the Single Subject Research (SSR) method through an A-B-A design, the research stages included initial observation, intervention, and ability evaluation. Data were collected through a performance test instrument that was measured repeatedly. The results showed a significant improvement in the subjects' abilities; in the initial baseline phase (A1), the average score was only 27.5%, then jumped to 64.2% during the intervention phase (B), and remained stable and high in the second baseline phase (A2) with an average of 76.6%. These findings demonstrate that dynamic visual media can attract attention and facilitate cognitive information processing in children on the autism spectrum. The main conclusion states that integrating animated posters into learning is very effective in helping students recognize body parts in a concrete and enjoyable way. This innovation makes a significant contribution to the development of adaptive instructional media in special schools, while also demonstrating that a structured visual approach can bridge communication and understanding barriers for students with special needs, optimally supporting their independent self-identification in an inclusive, integrated, and comprehensive formal education environment.